2011
DOI: 10.1002/gj.1309
|View full text |Cite
|
Sign up to set email alerts
|

Origin and diamond prospectivity of Mesoproterozoic kimberlites from the Narayanpet field, Eastern Dharwar Craton, southern India: insights from groundmass mineralogy, bulk‐chemistry and perovskite oxybarometry

Abstract: The Mesoproterozoic Narayanpet Kimberlite Field (NKF) is located~200 km north of the well-known Wajrakarur Kimberlite Field (WKF) in the Eastern Dharwar Craton, southern India. Whereas a majority of the WKF occurrences are diamondiferous and contain mantle xenoliths and xenocrysts, their paucity is a characteristic feature of the NKF. This has been attributed alternately to the derivation of NKF magmas from a shallower depth, or to variability in thickness of the Sub-Continental Lithospheric Mantle (SCLM) bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 82 publications
(195 reference statements)
0
7
0
Order By: Relevance
“…Narayanpet kimberlite field (NKF) is one of the major kimberlite field of Dharwar craton and occurring at the eastern part of Dharwar craton. The NKF Kimberlites, in general, are very small bodies and these kimberlites lack mantle xenoliths [25]. Narayanpet kimberlites are emplaced in granodiorites and gneisses and structurally controlled by E-W and NE-SW trending lineament [15].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Narayanpet kimberlite field (NKF) is one of the major kimberlite field of Dharwar craton and occurring at the eastern part of Dharwar craton. The NKF Kimberlites, in general, are very small bodies and these kimberlites lack mantle xenoliths [25]. Narayanpet kimberlites are emplaced in granodiorites and gneisses and structurally controlled by E-W and NE-SW trending lineament [15].…”
Section: Study Areamentioning
confidence: 99%
“…However, the ASTER convolved spectral profile of olivine rich kimberlite is featureless (Figure 3). Further, laboratory spectral profiles of kimberlites are convolved to ASTER bandwidth of SWIR channels for spatial mapping of kimberlite using sub pixel algorithm as the exposures of Narayanpet kimberlites are very small in size in comparison to the pixel size of ASTER data [25]. As the ASTER convolved laboratory spectral profiles of serpentinised and carbonate rich kimberlites are characterised with an absorption feature at around 2.33 micrometer ( Figure 3); hence, mean of ASTER convolved spectral profile carbonate and serpentine-rich kimberlite is used as a single end member for targeting the kimberlite based on sub-pixel mapping algorithm (Figure 3).…”
Section: Spatial Mapping Of Kimberlitementioning
confidence: 99%
“…Chalapathi Rao et al . () investigate the kimberlites from the Narayanpet Kimberlite Field and suggest that the low diamond potential in this region could be related to magmatic emplacement history, rather than to the depth of magma generation or extant redox conditions. Jayananda et al .…”
mentioning
confidence: 99%
“…The findings of our study are also consistent with those reported earlier by (i) Jha et al, (2002) wherein pyrope population in the Mainpur pipes has been inferred to be dominated by calcic-lherzolite variety corresponding to G9 and some eclogitic (G3, G4 and G5) and iron-titanian-low calcium (G1 and G2) garnets with the sub-calcic harzburgitic category (G10) pyrope garnet population between 1 and 5% and (ii) Mukherjee et al, (2000) who reported garnets of eclogitic paragenesis from the Behradih pipe. , 2004;Chalapathi Rao and Srivastava, 2009;Chalapathi Rao and Dongre, 2009;Chalapathi Rao et al, 2011b). and Brazil (McDonald et al, 1995) and China (Zhang et al, 2010).…”
mentioning
confidence: 99%
“…Oxygen fugacity (fO 2 ) (NNO) conditions of the Behradih and Kodomali orangeites compared with those recorded by cratonic mantle lithosphere, mantle-derived magmas and global kimberlites (adapted fromCanil and Bellis, 2007). Data for Dutoitspan kimberlites is fromOgilvie-Harris et al, (2009); NKF kimberlites(Chalapathi Rao et al, 2011b).…”
mentioning
confidence: 99%